Eksplorasi Penggunaan Video Animasi dalam menumbuhkan minat Pembelajaran Sejarah Kebudayaan Islam di MI Alkhairaat Biromaru, Kabupaten Sigi, Sulawesi Tengah, Indonesia: Exploring the Use of Animated Videos in Cultivating Students’ Interest in Islamic Cultural History Learning at Madrasah Ibtidaiyah Biromaru, Sigi Regency, Central Sulawesi, Indonesia - Rina, Rina; Takunas, Rusli; Nur, Rizka Fadliah (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
This study is motivated by the low learning interest of students in the subject of Islamic Cultural History (SKI). The conventional learning approach used by teachers is considered less attractive to students. To overcome this, teachers began using animated videos as learning media to convey material more engagingly. This study aims to examine how the application of animated video learning can increase students' interest in SKI, and what supporting and inhibiting factors are involved. The research used a qualitative approach with data collection techniques including observation, interviews, and documentation. The results showed that the implementation of animated video learning followed the stages of teaching well and succeeded in increasing students’ attention, enthusiasm, and active participation. Supporting factors include its ability to attract attention and make learning more enjoyable, while inhibiting factors include limited facilities and unstable internet. This research suggests that SKI teachers should continue developing the use of animated videos to create more effective and enjoyable learning experiences.